TAFSSA District Agrifood Systems Assessment in Bangladesh 2023: Male - International Food Policy Research Institute (International Food Policy Research Institute, 2024)
TAFSSA (Transforming Agrifood Systems in South Asia) is a CGIAR Regional Integrated Initiative aimed at supporting actions that improve equitable access to sustainable healthy diets, enhance farmers’ livelihoods and resilience, and conserve land, air, and water resources in South Asia. The TAFSSA district agrifood systems assessment seeks to provide a reliable, accessible, and integrated evidence base that connects farm production, market access, dietary patterns, climate risk responses, and natural resource management, with gender as a cross-cutting issue in rural areas of Bangladesh, India, and Nepal. It is designed as a district-level multi-year assessment. Data were collected in February-March 2023 in the Rangpur and Rajshahi districts in Bangladesh. Three respondents were interviewed per household: a female adult (aged 20+ years) primarily responsible for managing the household, a male adult (aged 20+ years) primarily responsible for agricultural activities, and an adolescent (aged 10-19 years). The assessment also included a community questionnaire, which interviewed a key informant in the district villages. The interviews with male household respondents were conducted using pretested, structured questionnaires. Information was gathered on food intake in the past 24 hours, household composition, agricultural land and activities, crop production and sales, homestead crops, livestock, fish cultivation, future farming aspirations, climate risk and adaptation, asset ownership, access to amenities, social safety net programs, organization membership, migration, and access to credit.